Luteinizing Hormone Involvement in Aging Female Cognition: Not All Is Estrogen Loss - Bhatta, Sabina; Blair, Jeffrey A.; Casadesus, Gemma (Frontiers in Endocrinology, 2018)
Pervasive age-related dysfunction in hypothalamic-pituitary-gonadal (HPG) axis is associated with cognitive impairments in aging as well as pathogenesis of age-related neurodegenerative diseases such as the Alzheimer’s disease (AD). As a major regulator of the HPG axis, the steroid hormone estrogen has been widely studied for its role in regulation of memory. Although estrogen modulates both cognition as well as cognition associated morphological components in a healthy state, the benefits of estrogen replacement therapy on cognition and disease seem to diminish with advancing age. Emerging data suggests an important role for luteinizing hormone (LH) in CNS function, which is another component of the HPG axis that becomes dysregulated during aging, particularly in menopause. The goal of this review is to highlight the current existing literature on LH and provide new insights on possible mechanisms of its action.